The effect of nursery production system (in cage and pond) on performance, health status, and plankton ingestion of the low trophic level fish tambaqui, Colossoma macropomum - Lima, Adriana Ferreira; Pereira, André Silvério; Costa-Fernandes, Thaís de Oliveira; Rodrigues, Ana Paula Oeda; Costa, Vladimir Eliodoro [UNESP]; Maciel-Honda, Patricia Oliveira (Elsevier, 2024)
The objective of the present study is to assess the growth performance, health condition, natural food intake, muscle fiber profile and isotopic composition of tambaqui, reared for 56 days in different production systems. Tambaqui fish (1.18 ± 0.55 g; 4.49 ± 0.66 cm) were stocked in 600 m2 earthen ponds (P), 3.6 m3 cages within earthen ponds (CP) and 15.68 m3 cages in a large water reservoir (C), at densities of 9 fish m−2 in P and 170 fish m−3 in C and CP. After 28 days of culture, the weight of fish reared in CP was lower than those in P and in C, with no difference between fish in P and C. Low water dissolved oxygen concentrations and, consequently, reduced growth were observed in fish reared in P from day 28. By day 56, fish in C presented high final weight (57.19 g). Best feed conversion ratio was observed in C (0.92) and CP (0.95), with no difference between these two treatments. Survival rate was not affected by the production systems. Zooplankton corresponded to 1.47%, 19.23% and 9.11% of δ13C assimilated by fish reared in C, CP and P, respectively. Increased mean abundance of monogeneans was observed in all treatments. >70% of fish reared in C presented fin damage, whereas in P and CP it was of 5% and 25%, respectively. After 56 days, cortisol concentration was higher in fish reared in C. Albumin, cholesterol, and total proteins were higher in fish reared in P. Muscle fiber hyperplasia (diameter < 30 μm) was predominant in fish in all treatments. Based on the results, tambaqui may be produces in cages and ponds. However, ponds demand more attention to avoid opportunistic fish entrance and to control parasitic infestations and water oxygen levels.
Keywords: Blood parameters; Isotopic analysis; Muscle fiber diameter; Natural food intake; Parasitology; Periphyton